Optimization of Electroless Ni-P-W Coatings for Minimum Friction and Wear Using Grey-Taguchi Method. (25th December 2013) - Roy, Supriyo; Sahoo, Prasanta
Abstract : The present experimental investigation deals with the deposition of electroless Ni-P-W coating on mild steel substrate and optimization of tribological parameters for better tribological behaviour like minimization of wear depth and coefficient of friction. Three tribological test parameters, namely, load, speed, and time, are optimized for minimum friction and wear of the coating. Friction and wear tests are carried out in a multitribotester using block on roller configuration under dry conditions. Taguchi based grey relational analysis is employed for optimization of this multiple response problem using L27 orthogonal array. Analysis of variance shows that load, speed, time, and interaction between load and speed have significant influence on controlling the friction and wear behavior of Ni-P-W coating. It is observed that wear mechanism is mild adhesive in nature. The structural morphology, composition, and phase structure of the coating are studied with the help of scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and X-ray diffraction analysis (XRD), respectively.